ANALYSIS OF THE IMPACT OF DIGITAL TRANSFORMATION ON THE MARKETING PERFORMANCE OF F&B SMES IN SURAKARTA, MEDIATED BY BUSINESS MODEL INNOVATION AS A SUPPORT FOR IMPROVING MARKETING PERFORMANCE IN F&B SMES IN SURAKARTA - Ade Rakhman Muhammad Rokhim; Aflit Nuryulia Praswati (Jurnal Ekonomi, 2023)
In the present era, digital transformation has become a means of development in the economic and business sectors, including in the field of F&B (Food and Beverage), as well as in SMEs (Small and Medium Enterprises) operating in the F&B sector. This research discusses the influence of digital transformation on the marketing performance of F&B products in the Surakarta region. This study employs a quantitative approach and utilizes purposive sampling techniques for data collection. The population of this research consists of F&B SME operators in Surakarta. In this study, Partial Least Squares Structural Equation Modeling (PLS-SEM) is used for data analysis. The results of the analysis conducted using PLS-SEM indicate that Marketing Performance can be influenced by several factors, namely Digital Transformation and BMI (Business Model Innovation), where explorative digital transformation has the most significant impact on Marketing Performance. Therefore, this study answers the fundamental question of whether implementing Digital Transformation will affect the Marketing Performance of every product sold or produced by F&B SME operators, providing evidence that Digital Transformation is a strong antecedent to Marketing Performance.